Workload And Job Boredom In Driving Quiet Quitting Among Generation Z Employees In Bekasi City: The Mediating Role Of Job Satisfaction - Ibnu Haris Nasution; Agtovia Frimayasa; Anton Kurniawan (Journal Arbitrase : Economy, Management and Accounting, 2026)
This study aims to examine the influence of workload and job boredom on quiet quitting behavior among Generation Z employees, with job satisfaction acting as a mediating variable. The research is grounded in the increasing phenomenon of employee disengagement, particularly among younger workers who tend to prioritize work-life balance, psychological well-being, and meaningful work experiences. A quantitative approach with an explanatory research design was employed to analyze the relationships among the variables. Data were collected from Generation Z employees working in Bekasi City using a structured questionnaire. The analysis was conducted using Structural Equation Modeling based on Partial Least Squares to evaluate both the measurement and structural models. The findings indicate that workload and job boredom significantly influence job satisfaction and quiet quitting behavior. High workload tends to reduce job satisfaction and increase disengagement, while job boredom contributes to lower motivation and diminished work involvement. Job satisfaction is found to play a crucial mediating role, where higher satisfaction levels reduce the likelihood of quiet quitting behavior. This study contributes to the literature on organizational behavior by providing a comprehensive understanding of the factors influencing quiet quitting among Generation Z employees. The results also offer practical implications for organizations to design effective human resource strategies by managing workload, reducing job monotony, and enhancing employee satisfaction to improve engagement and organizational performance.